Cost-effectiveness of HPV vaccination for adults through age 45 years in the United States: Estimates from a simplified transmission model. Issue 50 (25th November 2020) - Chesson, Harrell W.; Meites, Elissa; Ekwueme, Donatus U.; Saraiya, Mona; Markowitz, Lauri E.
Abstract: Introduction: The objective of this study was to assess incremental costs and benefits of a human papillomavirus (HPV) vaccination program expanded to include "mid-adults" (adults aged 27 through 45 years) in the United States. Methods: We adapted a previously published, dynamic mathematical model of HPV transmission and HPV-associated disease to estimate the incremental costs and benefits of a 9-valent HPV vaccine (9vHPV) program for people aged 12 through 45 years compared to a 9vHPV program for females aged 12 through 26 years and males aged 12 through 21 years. Results: A 9vHPV program for females aged 12 through 26 years and males aged 12 through 21 years was estimated to cost < 10, 000 quality-adjusted life year (QALY) gained, compared to no vaccination. Expanding the 9vHPV program to include mid-adults was estimated to cost 587, 600 per additional QALY gained when including adults through age 30 years, and 653, 300 per additional QALY gained when including adults through age 45 years. Results were most sensitive to assumptions about HPV incidence among mid-adults, current and historical vaccination coverage, vaccine price, and the impact of HPV diseases on quality of life. Conclusions: Mid-adult vaccination is much less cost-effective than the comparison strategy of routine vaccination for all adolescents at ages 11 to 12 years and catch-up vaccination for women through age 26 years and men through age 21 years.